Bundling and joint marketing by rival firms. Issue 3 (7th March 2017) - Jeitschko, Thomas D.; Jung, Yeonjei; Kim, Jaesoo
Abstract: We study joint marketing by firms who price discriminate between consumers who patronize only one firm (single purchasers) and those who purchase from both (bundle purchasers). Firms either set the price of the bundle and then compete along side the bundle; or they determine a rebate that is applied to joint purchasers and then set prices. Even though the pricing structure in the joint marketing scheme is determined noncooperatively, the commitment to the joint marketing agreement allows firms to leverage their stand‐alone prices—leading to higher profits and lower consumer surplus in either case, compared to both uniform pricing and independent price discrimination without a joint marketing agreement. Nevertheless the two schemes differ dramatically, in that rebates increase joint purchasing, whereas bundle pricing diminishes bundle purchases.